2001
DOI: 10.1890/0012-9658(2001)082[1023:tiomip]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Multiple Introduced Predators on a Littoral Pond Community

Abstract: In a replicated field experiment we studied the effects of natural densities of two exotic consumers, the predatory and herbivorous signal crayfish (Pacifastacus leniusculus) and the predatory rainbow trout (Oncorhynchus mykiss), on multiple trophic levels of a pond community. The goals were to: (1) determine the individual and combined effects of predators on macroinvertebrates, macrophytes, and periphytic algae; (2) evaluate the strength of direct and indirect interactions in a food web influenced by omnivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
113
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 103 publications
7
113
0
8
Order By: Relevance
“…These results show that introduced across Europe, where impacts upon aquatic flora and fauna have been extensively documented (e.g. Unestam and Weiss 1970;Nyström et al 2001;Stenroth and Nyström 2003;Bubb et al 2006;Olden et al 2006;Bubb et al 2009;Axelsson et al 1997).…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…These results show that introduced across Europe, where impacts upon aquatic flora and fauna have been extensively documented (e.g. Unestam and Weiss 1970;Nyström et al 2001;Stenroth and Nyström 2003;Bubb et al 2006;Olden et al 2006;Bubb et al 2009;Axelsson et al 1997).…”
Section: Introductionsupporting
confidence: 53%
“…Both native and invasive crayfish can affect plant and animal communities through predation (e.g. Charlebois and Lamberti 1996;Axelsson et al 1997;Parkyn et al 1997;Nyström et al 2001;Dorn and Mittelbach 2004;Usio and Townsend 2004;McCarthy et al 2006;Jackson et al 2014;Moorhouse et al 2014), demonstrated by their consistently strong negative effects on plant biomass, other macroinvertebrates, fish and amphibian eggs and larvae. Additionally, crayfish are likely to directly compete with other organisms for resources (Bubb et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies documenting the effect of invasive crayfish in stream ecosystems have identified significant reductions in the biomass and richness of aquatic macrophytes Nyström et al, 2001), and aquatic invertebrates Stenroth and Nyström, 2003;Crawford et al, 2006;Nilsson et al, 2012;Ercoli et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%